Circular RNAs as novel regulators of β-cell functions in normal and disease conditions - Lisa Stoll; Jonathan Sobel; Adriana Rodriguez-Trejo; Claudiane Guay; Kailun Lee; Morten Trillingsgaard Venø; Jørgen Kjems; D. Ross Laybutt; Romano Regazzi (Elsevier, 2018)
Objective: There is strong evidence for an involvement of different classes of non-coding RNAs, including microRNAs and long non-coding RNAs, in the regulation of β-cell activities and in diabetes development. Circular RNAs were recently discovered to constitute a substantial fraction of the mammalian transcriptome but the contribution of these non-coding RNAs in physiological and disease processes remains largely unknown. The goal of this study was to identify the circular RNAs expressed in pancreatic islets and to elucidate their possible role in the control of β-cells functions. Methods: We used a microarray approach to identify circular RNAs expressed in human islets and searched their orthologues in RNA sequencing data from mouse islets. We then measured the level of four selected circular RNAs in the islets of different Type 1 and Type 2 diabetes models and analyzed the role of these circular transcripts in the regulation of insulin secretion, β-cell proliferation, and apoptosis. Results: We identified thousands of circular RNAs expressed in human pancreatic islets, 497 of which were conserved in mouse islets. The level of two of these circular transcripts, circHIPK3 and ciRS-7/CDR1as, was found to be reduced in the islets of diabetic db/db mice. Mimicking this decrease in the islets of wild type animals resulted in impaired insulin secretion, reduced β-cell proliferation, and survival. ciRS-7/CDR1as has been previously proposed to function by blocking miR-7. Transcriptomic analysis revealed that circHIPK3 acts by sequestering a group of microRNAs, including miR-124-3p and miR-338-3p, and by regulating the expression of key β-cell genes, such as Slc2a2, Akt1, and Mtpn. Conclusions: Our findings point to circular RNAs as novel regulators of β-cell activities and suggest an involvement of this novel class of non-coding RNAs in β-cell dysfunction under diabetic conditions. Keywords: Circular RNA, Diabetes, Insulin, microRNA, Pancreatic islet